Stories we've heard, stories we've told : life-changing narratives in therapy and everyday life - Kottler, Jeffrey A. (Oxford University Press, 2015)
This is a book that integrates what is known from a wide variety of disciplines about the nature of storytelling and how it influences and transforms people''s lives. Drawing on material from the humanities, sociology, anthropology, neurophysiology, media and communication studies, narrative inquiry, Indigenous healing traditions, as well as education, counseling, and therapy, the book explores the ways that therapists operate as professional storytellers. In addition, our job is to hold and honor the stories of our clients, helping them to reshape them in more constructive ways.